"Poor, Proud and Pretty" Community History and the Challenge of Heritage in "Darkest" Cheltenham. (2nd January 2020) - O'Connell, Christian
ABSTRACT: The article discusses a collaborative local history project in Cheltenham Spa's Lower High Street, an area that has suffered from "symbolic annihilation" through a long history of stigmatisation at the expense the town's Regency-era heritage. Residents' testimonies give voice to marginalised experiences that help to establish the area's distinctive "sense of place, " which is rooted in shared experiences of exclusion, hardship and community cohesion. Through nostalgic recollections, they also reveal a significant grassroots willingness to challenge the exclusionary practices of Cheltenham's dominant and exclusionary Regency narrative. However, present concerns about ethnic diversity and urban decay also exposed contemporary anxieties that are indicative of the broader context of Britain in the EU referendum era. While offering a "history from below, " the paper also considers how universities operating as "anchor" institutions can help to address contemporary issues of social alienation and spatial inequality by fostering a greater appreciation of the past.